2021
DOI: 10.3390/ijms222413256
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Retromer Function in Niemann-Pick Type C Disease Is Dependent on Intracellular Cholesterol Accumulation

Abstract: Niemann-Pick type C disease (NPC) is a rare inherited neurodegenerative disorder characterized by an accumulation of intracellular cholesterol within late endosomes and lysosomes due to NPC1 or NPC2 dysfunction. In this work, we tested the hypothesis that retromer impairment may be involved in the pathogenesis of NPC and may contribute to increased amyloidogenic processing of APP and enhanced BACE1-mediated proteolysis observed in NPC disease. Using NPC1-null cells, primary mouse NPC1-deficient neurons and NPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Immunocytochemistry on HeLa and MJ90 cells was performed as previously described [ 114 ]. In short, the cells grown on coverslips were washed three times in the PBS and fixed with 4% sucrose/paraformaldehyde for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry on HeLa and MJ90 cells was performed as previously described [ 114 ]. In short, the cells grown on coverslips were washed three times in the PBS and fixed with 4% sucrose/paraformaldehyde for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Control cells were co-transfected with empty-GFP (pEGFP-N1) and empty-CHERRY (pmCherry - C1) vector, respectively. Immunocytochemistry on MCF-7 cells was performed as previously described 70 . In short, the cells grown on coverslips were washed three times in PBS, fixed with 4% sucrose/paraformaldehyde for 15 min and permeabilized with 0.2% saponin in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…We found that CD63 KO increases the recruitment of VPS35 on endosomes. Cholesterol availability at the limiting membrane of endosomes in absence of CD63 might control actin bundling and retromer recruitment 56,57 . This process could also rely on the potential interaction between CD63 and PI4-kinase 58 and the recent implication of this family of enzyme and PI4P in endosomal tubule formation driven by actin and retromer 59,60 .…”
Section: Discussionmentioning
confidence: 99%